HUBUNGAN ANTARA TEOLOGI DAN PENDIDIKAN AGAMA KRISTEN: PERANAN PENDIDIKAN AGAMA KRISTEN DAN GENDER - Udur Ernita Aritonang; Wilson Rajagukguk; Thomas Pentury (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the relationship between theology and Christian Religious Education (CRE) by highlighting the role of CRE in gender education and its implementation at HKBP Pabrik Tenun Medan. CRE not only serves as an instrument for teaching the Christian faith but also as a medium for social transformation, particularly in shaping a more just gender awareness within the church and society. In the context of Christian theology, understandings of gender are often influenced by biblical interpretation, church doctrine, and local culture. Therefore, this study explores how CRE in this church responds to gender issues, particularly in promoting equal roles between men and women in ministry and the congregation’s participation in church leadership. The church has a responsibility to teach the values of equality, justice, and respect for gender differences in accordance with biblical principles. However, in practice, challenges remain, particularly in the form of patriarchal interpretations that may limit women's roles in ecclesiastical ministry. This study also highlights how the church can develop a more inclusive CRE theology by incorporating gender perspectives based on liberation theology and justice. This research employs a qualitative and descriptive method, utilizing in-depth interviews, participatory observations, and document analysis to obtain comprehensive data. The findings indicate that, despite efforts by CRE to teach gender equality, challenges persist in its implementation due to cultural and traditional factors, particularly the strong influence of the highly patriarchal Batak Toba culture. Therefore, this study is expected to serve as a reference for churches in designing CRE programs that are more responsive to gender issues, encouraging active female participation in church life and ministry.